Burkhart House, Ketchikan, Alaska, 1929-1930 - Unidentified
Home is located at 500 Main St., Ketchikan, Alaska. It has the name of 'The Burkhart House' built in 1904. The home was renovated between 2005-2009 and put on the market by owner for $649,000 in 2014. Written on photograph: A home, Ketchikan PH Coll 1331.3c